THE USE OF INITIATION-RESPONSE-FEEDBACK PATTERN IN CONTENT-LANGUAGE INTEGRATED LEARNING CLASSROOM INTERACTION : CASE-STUDY AT RSBI SCHOOL IN BANDUNG - Ramadhan, Muh. Aditya Gilang (2012)
In regards to the RSBI guidelines proposed by Kemendiknas, RSBI schools must conduct bilingual classes, which involve two different languages as the classroom language. In this case, Bahasa Indonesia is used as native language and English as a second language. In RSBI classes, some subjects require teachers to use English as target language. Therefore, the teachers who are non-native English teachers have to teach content subject using English. One of the approaches in teaching content subject in RSBI school is CLIL. Content and Language Integrated Learning (CLIL) means, in the process of teaching-learning in RSBI schools, teachers must deliver the content subject as well as delivering knowledge about the target language. This condition motivates the writer to focus the study on classroom interaction. One of the models of classroom interaction that can be found in CLIL class is Sinclair and Coulthard (1975) IRF (Initiation-Response-Feedback). The objectives of this study are to describe the IRF pattern happens in CLIL classroom interaction, the types of question used as an initiation moves and the code-switching between Bahasa Indonesia and English in CLIL classroom. The subjects of this study were one Biology teacher and her 9-A class, and one Physics teacher and his 9-G class. Based on the analysis of two teachers' lessons, it can be seen that IRF does characterize teacher-fronted classroom discourse. It was evident that the teachers dominantly steered the classroom interaction by placing themselves as the most frequent initiator. The use of elicit in initiation slot provides more chances to complete the IRF pattern. By putting more elicit, students are strongly requested to respond to the initiation. This happened because Physics does use number and measurement. This study also found 6 types of feedback done by those two teachers; acknowledgement, correction, expansion, reformulation, translation and repetition. Then, this study presents the elicit acts which were classified into four types of questions. First is display or referential question, then the use of open-ended or closed questions, low-level questions or high-level questions and last is based on the function questions themselves. Moreover, the study also presents the use of code-switching in CLIL classroom. It provides a brief discussion and description of how did they code-switch from Bahasa Indonesia to English and vice versa. Furthermore, this study presents the use of language through the IRF pattern which might be different from non-CLIL classroom. Keywords: Content and Language Integrated Learning (CLIL), Rintisan Sekolah Bertaraf Internasional (RSBI), Initiation-Response-Feedback (IRF)